Echo- and B-Type Natriuretic Peptide-Guided Follow-Up versus Symptom-Guided Follow-Up: Comparison of the Outcome in Ambulatory Heart Failure Patients. (30th September 2018) - Bajraktari, Gani; Pugliese, Nicola Riccardo; D'Agostino, Andreina; Rosa, Gian Marco; Ibrahimi, Pranvera; Perçuku, Luan; Miccoli, Mario; Galeotti, Gian Giacomo; Fabiani, Iacopo; Pedrinelli, Roberto; Henein, Michael; Dini, Frank L.
Abstract : Recent European Society of Cardiology and American Heart Association/American College of Cardiology Guidelines did not recommend biomarker-guided therapy in the management of heart failure (HF) patients. Combination of echo- and B-type natriuretic peptide (BNP) may be an alternative approach in guiding ambulatory HF management. Our aim was to determine whether a therapy guided by echo markers of left ventricular filling pressure (LVFP), lung ultrasound (LUS) assessment of B-lines, and BNP improves outcomes of HF patients. Consecutive outpatients with LV ejection fraction (EF) ≤ 50% have been prospectively enrolled. In Group I (n = 224 ), follow-up was guided by echo and BNP with the goal of achieving E-wave deceleration time (EDT) ≥ 150 ms, tissue Doppler index E / e ′ < 13, B-line numbers < 15, and BNP ≤ 125 pg/ml or decrease >30%; in Group II (n = 293 ), follow-up was clinically guided, while the remaining 277 patients (Group III) did not receive any dedicated follow-up. At 60 months, survival was 88% in Group I compared to 75% in Group II and 54% in Group III ( χ 2 53.5; p < 0.0001 ). Survival curves exhibited statistically significant differences using Mantel–Cox analysis. The number needed to treat to spare one death was 7.9 (Group I versus Group II) and 3.8 (Group I versus Group III). At multivariate Cox regression analyses, major predictors of all-cause mortality were follow-up E / e ′ (HR: 1.05; p = 0.0038 ) and BNP >125 pg/ml or decrease ≤30% (HR: 4.90; p = 0.0054 ), while BNP > 125 pg/ml or decrease ≤30% and B-line numbers ≥15 were associated with the combined end point of death and HF hospitalization. Evidence-based HF treatment guided by serum biomarkers and ultrasound with the goal of reducing elevated BNP and LVFP, and resolving pulmonary congestion was associated with better clinical outcomes and can be valuable in guiding ambulatory HF management.